WORKSHOP TECHNIQUE SUPERVISION TO IMPROVE TEACHERS’ PEDAGOGIC AND PROFESSIONAL COMPETENCE IN TEACHING AT SDN 18 BATANG BARUS, KABUPATEN SOLOK - Jonrivisman; Ahmad F, Farida F (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was initiated by the lack of teachers’ pedagogical and professional competence at SDN 18 Batang Barus in performing the teaching and learning process. The research aimed to describe the implementation of workshop technique supervision to enhance the pedagogical and professional competence of the classroom teachers at SDN 18 Batang Barus. The method of this research was school action research which was conducted in 2 cycles at the end of semester I academic year 2017/2018. This research involved 9 classroom teachers as the research subjects. The research data were collected through the observation of the implementation of workshop technique supervision and the assessment of pedagogical and professional competence of classroom teachers. The results showed that the implementation of workshop technique supervision at SDN 18 Batang Barus followed the procedures which was divided into four main steps: (1) planning, including setting workshop goals (output to be achieved), formulating the main points, determining the troubleshooting procedures, and determining tools and supplies used during the workshop, (2) implementation, (3) observation, and (4) reflection including formulating the difficulties faced and formulating an action plan as a follow up activities. After applying workshop technique supervision, this research revealed an increase of pedagogical competence of the classroom teachers at SDN 18 Batang Barus, which was initially 51.61 and increased to 69.40 in cycle I and became 86.05 in cycle II. Moreover, it was also found an improvement of the professional competence of the classroom teachers after applying workshop technique supervision, which was initially 43.75 and increased to 65.19 in cycle I and became 86.11 in cycle II. Based on the research findings, it was concluded that workshop technique supervision could be used as an alternative way to do supervision for teachers who mostly faced the same problems.Keywords: , , ,